Cadmium and lead content in gluten and gluten-free bread available on the Polish market – potential health risk to consumers - Magdalena Gacal; Klaudia Gut-Pietrasz; Małgorzata Ćwieląg-Drabek (Annales Academiae Medicae Silesiensis, 2023)
Introduction: Grain products, especially bread, play an essential role in the nutrition of people around the world. However, due to the release of excessive amounts of pollutants into the environment, grain products may also contain some amounts of potentially toxic elements, which may have a negative effect on the human body. Material and methods: The aim of the study is to analyze the content of heavy metals in selected gluten and gluten-free breads available on the Polish market, and to assess the non-cancerous and cancerous exposure of consumers to cadmium (Cd) and lead (Pb). This assessment covered the exposure of eight age groups. The content of Cd and Pb was determined by the ET-AAS method. Results: The highest mean concentration of Cd was recorded in wheat-rye bread (0.072 mg/kg), the lowest in gluten-free bread (0.021 mg/kg). The general distribution of Cd in individual types of bread was as follows: wheat-rye > wheat > rye > gluten-free bread. Conclusions: The estimation of exposure to Cd and Pb of the consumers of wheat and wheat-rye bread showed that a significant health risk may occur in the population of children < 11 years of age.